In vivo Imaging of Glial Activation in Alzheimer's Disease - Edison, Paul; Donat, Cornelius K.; Sastre, Magdalena (Frontiers in Neurology, 2018)
Alzheimer's disease (AD) is characterized by memory loss and decline of cognitive function, associated with progressive neurodegeneration. While neuropathological processes like amyloid plaques and tau neurofibrillary tangles have been linked to neuronal death in AD, the precise role of glial activation on disease progression is still debated. It was suggested that neuroinflammation could occur well ahead of amyloid deposition and may be responsible for clearing amyloid, having a neuroprotective effect; however, later in the disease, glial activation could become deleterious, contributing to neuronal toxicity. Recent genetic and preclinical studies suggest that the different activation states of microglia and astrocytes are complex, not as polarized as previously thought, and that the heterogeneity in their phenotype can switch during disease progression. In the last few years, new in vivo imaging techniques including new tracers for microglia and astrocytes by positron emission tomography and magnetic resonance imaging technology have emerged, allowing the correlation of neuro-inflammatory markers with cognitive decline, brain function and brain pathology in vivo. Here we review all new imaging technology in AD patients and animal models that has the potential to serve for early diagnosis of the disease, to monitor disease progression and to test the efficacy and the most effective time window for potential anti-inflammatory treatments.